Ectopic pregnancy in simultaneous pancreas-kidney transplantation: A case report - Yamamoto, Shinji (Elsevier, 2016)
•We report a case r of ectopic pregnancy after simultaneous pancreas-kidney transplantation.•Ectopic pregnancy should be included in the different diagnosis in simultaneous pancreas-kidney transplantation female patients who get acute abdominal pain.•Transplanted pancreas in abdomen is easily misrecognized as adipose tissue and there is high risk that the organ to get injured surgically.•The operation resulted in satisfactory results without any kind of complications.